Polymerase Gamma Mitochondrial DNA Depletion Syndrome Initially Presenting as Disproportionate Respiratory Distress in a Moderately Premature Neonate: A Case Report - Franklin, Andrew D.; Chaudhari, Bimal P.; Koboldt, Daniel C.; Machut, Kerri Z. (Frontiers in Genetics, 2021)
A 32-week premature infant presented with respiratory failure, later progressing to pulmonary hypertension, liver failure, lactic acidosis, and encephalopathy. Using whole exome sequencing, this patient was diagnosed with a rare POLG-related mtDNA depletion syndrome. This case demonstrates that expanding the differential to uncommon diagnoses is important for complex infants, even in premature neonates whose condition may be explained partially by their gestational age. It also shows that patients with complex neonatal diseases with significant family history may benefit from whole exome sequencing for diagnosis.